The potential of South Africa's "Boers": Dutch immigrant farmer to modern-day Afrikaner entrepreneur. Issue 1 (15th November 2018) - Lloyd, Warren
Abstract : Purpose: Due to the limited research on minority entrepreneurs in Africa, this paper aims to investigate the specific motivation of the current-day Afrikaner community group in South Africa toward entrepreneurship, whether necessity- or opportunity-based, as they represent a valuable potential toward not just economic growth but a wealth of entrepreneurial cultural capital capable of partnering and sharing successfully with other ethnic community groups. Design/methodology/approach: The empirical research was conducted by quantitative analysis where data were gathered from a random sample of 648 respondents of an online survey. The ten-item achievement motives scale (AMS-R) was used to measure the distinct hope of success (HS) and fear of failure (FF) motives in McClelland's need for achievement (nAch). The survey was conducted by the writer as part of an alternative study, and the data were analysed using SPSS v23. Findings: The research determined no significant differences between HS (opportunity motivation) between specified age groups, but for FF (necessity motivation), there were statistical differences. This then disproved the stated hypothesis that current and nascent Afrikaner entrepreneurs are indifferent between the two motives. Along with this, it was found that there exists an overall high HS motive in the Afrikaner community, suggesting a high propensity toward the desired opportunity motivated entrepreneurship. Research limitations/implications: This research is limited to nAch motivation within the single minority group of Afrikaners in South Africa. Implications for future research could be further comparison to other groups, both minority immigrant and "home" cultural groups, and the value of this as it relates to economic growth and knowledge sharing contexts. Practical implications: The overall high HS motivation seen in the results should be reassuring for policymakers, on the basis that opportunity motivation is a key driver of economic growth and the value as it relates to knowledge sharing from the Afrikaner group to poorer community groups. Social implications: South Africa, with a large poor community, and one of the lowest entrepreneurial rates in the world, is desperately in need of economic growth that the potential of partnerships with Afrikaner entrepreneurs contain, both from economic growth and knowledge sharing contexts. The high-opportunity-motivated entrepreneurship seen in the Afrikaners community suggests that there exists the willingness for such partnerships. Originality/value: This paper provides empirical confirmation of the high opportunity entrepreneurial motive in nascent Afrikaners and provides a positive motivation for developing policies to harness this opportunity through initiatives and partnerships linking Afrikaner and black communities.